Analysis of Effect of Auditor Quality, Liquidity, Profitability, and Solvency on Going Concern Audit Opinions in Manufacturing Companies in the Basic and Chemical Industry Sub-Sectors Listed on the Indonesia Stock Exchange in 2017-2019 - Salim, Karyn; Wynne, Wynne; Simorangkir, Enda Noviyanti (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The purpose of this study was to determine and analyze auditor quality, liquidity, profitability, and solvency on going concern audit opinions in Manufacturing Companies in the Basic and Chemical Industry Sub-Sectors listed on the Indonesia Stock Exchange in 2017-2019. The method used in this research is descriptive and quantitative. The data in this study are secondary data. The population in this study is the Manufacturing Companies in the Basic and Chemical Industry Sub-Sectors listed on the Indonesian Stock Exchange in 2017-2019, which are 77 companies. Samples that meet the criteria are 41 companies or 123 research data by using purposive sampling in sampling. The data were analyzed using descriptive statistical analysis and logistic regression. The results of the research on descriptive statistics prove that the research that has been examined from companies that have been sorted obtain going concern as many as 38 samples of companies while non going concern as many as 85 samples of companies. The results of the research on logistic regression state that auditor quality, profitability, and solvency have a positive effect on going concern audit opinions with a significant level of 0.05, while liquidity does not has a positive effect on going concern audit opinions with a significant level of 0.05.